Engineering 'Posthumans': To Be or Not to Be?. Issue 8 (August 2017) - Karamanou, Marianna; Papaioannou, Theodore G.; Soulis, Dimitrios; Tousoulis, Dimitrios
Abstract : Emerging technological innovations have transformed some science fiction ideas into reality, promising radical changes in human nature. New philosophical and intellectual movements such as 'transhumanism' and 'posthumanism' try to foretell and even direct the future of our existence while dealing with new and complex ethical, social, political issues and dilemmas.